2022
DOI: 10.3389/fphar.2022.953438
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of traditional Chinese herbal-based formulations Jing Si herbal tea and Jing Si nasal drop inhibits adhesion and transmission of SARS-CoV2 in diabetic SKH-1 mice

Abstract: Multiple studies show increased severity of SARS-CoV2-infection in patients with comorbidities such as hypertension and diabetes. In this study, we have prepared two herbal-based formulations, a pleiotropic herbal drink (Jin Si Herbal Tea, JHT) and a nasal drop (Jin Si nasal drop, JND), to provide preventive care against SARS-CoV2 infection. The effect of JHT and JND was determined in SARS-CoV2-S-pseudotyped lentivirus-infected bronchial and colorectal cell lines and in SKH-1 mouse models. For preliminary stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 42 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…In addition, five major flavonoids Jaceosidin, Eupatilin, Apigenin, Eupafolin, and 5,6-Dihydroxy-7,3′,4′-trimethoxyflavone, of A. argyi , have been predicted to be the potential inhibitors the main protease Mpro of COVID-19 [58] . Other constituents of JSHT such as H. cordata , O. caudate and G. uralensis were found to block the ACE2-spike protein binding and thereby inhibit of COVID-19 [32] , [59] , [60] , [61] , [62] . Previous reports partially attribute the antiviral activity to of O. caudata to their flavonoid content [59] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, five major flavonoids Jaceosidin, Eupatilin, Apigenin, Eupafolin, and 5,6-Dihydroxy-7,3′,4′-trimethoxyflavone, of A. argyi , have been predicted to be the potential inhibitors the main protease Mpro of COVID-19 [58] . Other constituents of JSHT such as H. cordata , O. caudate and G. uralensis were found to block the ACE2-spike protein binding and thereby inhibit of COVID-19 [32] , [59] , [60] , [61] , [62] . Previous reports partially attribute the antiviral activity to of O. caudata to their flavonoid content [59] .…”
Section: Discussionmentioning
confidence: 99%
“…Current TCM-based formulations known to treat COVID-19 patients were reported to act on multiple pathways and possess anti-viral, anti-inflammatory and immunoregulatory effects [32] , [53] , [54] , [55] , [56] . For example, Tsai et al, demonstrated the therapeutic effects of Taiwan Chingguan Yihau (NRICM101) [53] which include blocking the viral entry and cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous literature, Ohwia caudata (OC) and Artemisia argyi (AA) locally called chinse herbal medicines derived from these plants are used to treat several common human diseases, including bacillary dysentery and rheumatic arthritis which is known as folk medicine. Ohwia caudata (OC) belongs to the Fabaceae family under the genus Ohwia formally Desmodium ( Desmodium caudatum ) 10,11,15 . Artemisia argyi (AA) leaf extract is commonly used as traditional Chinese herbal medicine for several diseases, such as eczema.…”
Section: Introductionmentioning
confidence: 99%